Papel de citocinas, óxido nítrico sintase e ciclooxigenase-2 na mucosite intestinal induzida pelo cloridrato de irinotecano (cpt-11) – efeito da pentoxifilina, talidomida e celecoxibe - Melo, Maria Luisa Pereira de (2007)
Irinotecan (CPT-11) is an inhibitor of DNA topoisomerase I and clinically effective against several cancers. A major toxic effect of CPT-11 is delayed diarrhea; however, the exact mechanism by which the drug induces diarrhea has not been established. Purpose: The aim of the present study was to elucidate the involvement of cytokines (TNF-α, IL-1β and KC), nitric oxide (NO) and prostaglandins (PGs) in the pathogenesis of CPT-11-induced mucositis and the effects of the cytokine production inhibitors, pentoxifylline (PTX) and thalidomide (TLD), as well as the effects of the selective cyclooxygenase (COX-2) inhibitor, celecoxib (CLX), in the CPT-11 induced intestinal mucositis, in mice. Materials and methods: the animals were treated with CPT-11 (50, 75 or 100 mg/kg, i.p.) or vehicle (0,5 ml, i.p.) daily for four days, in order to investigate the best dose able to induce intestinal mucositis without important mortality. In another set of experiments, the animals received PTX (1.7, 5, 15 mg/kg, s.c.), TLD (15, 30, 60 mg/kg, s.c.), CLX (3, 10, 30 mg/kg, oral gavage) or vehicle (0,5 ml, s.c. or oral gavage) one day before the 1st administration of CPT-11 (75 mg/kg; i.p.) and daily until the sacrifice, on the 5th or 7th day. The systemic parameters evaluated were: diarrhea, body mass variation, survival curve and leucogram. In addition, it was also performed histological analysis, myeloperoxidase (MPO) activity assay, duodenum levels of TNF-α, IL-1β and KC by ELISA and immunohistochemistry for TNF-α, IL-1β, iNOS and COX-2 in the duodenal segments. Results: CPT-11 induced an important diarrhea, weight loss, leucopenia and mortality increase. It was also observed histopathological changes, such as shortened villi, loss of the crypt architecture and inflammatory cells infiltration, observed in the lamina propria, as well as, an increase in MPO activity, TNF-α, IL-1β and KC tissue levels and a marked immuno-staining for TNF-α, IL-1β, iNOS and COX-2. The treatment with PTX inhibited the delayed diarrhea and reduced the following parameters: histopathological alterations, MPO activity, tissue levels of TNF-α, IL-1β and KC, and the immuno-staining for TNF-α, IL-1β and iNOS, however, did not prevent leucopenia, weight loss and mortality. TLD significantly reduced all the inflammatory parameters evaluated, but was not able to prevent diarrhea, leucopenia, weight loss and mortality. On the other hand, CLX did not inhibit the inflammatory nor the systemic alterations induced by CPT-11. Conclusion: These results suggest an important role of TNF-α, IL-1β, KC, NO and PGs in the pathogenesis of intestinal mucositis induced by CPT-11. PTX and TLD showed a protector effect in intestinal structures, however, only PTX reduced the severity of CPT-11-induced diarrhea.